Herbicide efficacy on three annual grass weeds in soils with different cropping histories - Rahman, A.; James, T.K. (New Zealand Plant Protection, 2010)
The efficacy of several preemergence herbicides on barnyard grass (Echinochloa crusgalli) smooth witchgrass (Panicum dichotomiflorum) and yellow bristle grass (Setaria pumila) was investigated in different soils in pot experiments These soils were collected from the top 10 cm of seven maize fields with different cropping histories The herbicides used were dimethanamid alachlor metolachlor two formulations of acetochlor and proprietary mixes of acetochlor with atrazine or metribuzin Plastic pots filled with soil were seeded with 10 seeds of individual grass species and herbicide treatments were then applied with a precision pot sprayer A further 10 seeds of the same grass species were sown at 2weekly intervals for 8 weeks to test the duration of residual weed control The number of emerged seedlings was counted in each pot at 2 weeks after each planting Metolachlor was the most effective chemical for controlling E crusgalli and P dichotomiflorum For S pumila similar levels of control were achieved by all treatments evaluated Generally all the herbicides were less effective in soils with a long history of maize growing where up to three times more seedlings emerged than in soils with only 12 years of maize cropping